ダイ38ジ ナンキョク チイキ カンソク タイ キショウ ブモン ホウコク 1997 - 江崎, 雄治; エサキ, ユウジ; 栗田, 邦明; クリタ, クニアキ; 松島, 功; マツシマ, イサオ; 木津, 暢彦; キヅ, ノブヒコ; 中嶋, 哲二; ナカジマ, テツジ; 金戸, 進; カネト, ススム; et al. (2000)
P(論文) この報告は第38次南極地域観測隊気象部門が, 1997年2月1日から1998年1月31日まで昭和基地において, および, 1997年1月25日から1998年1月20日までドームふじ観測拠点において行った気象観測結果をまとめたものである。観測方法, 測器, 統計方法等は第37次観測隊とほぼ同様である。越冬期間中特記される気象現象として, 次のものがあげられる。1) 昭和基地での年平均気温はほぼ平年並みであった。9月の月平均気温は-23.6℃であり歴代1位の低さであった。2) 昭和基地において, 9年連続で大規模なオゾンホールを観測し, オゾン全量の最低月平均値は10月の164m atm-cmであった。これは観測開始以来2番目に低い記録であった。3) 昭和基地において, 1年を通して地上オゾン濃度観測を行った。8月28日から29日にかけて地上オゾン濃度急減現象を観測した。4) 昭和基地において, エアロゾルゾンデにより成層圏エアロゾルの観測を行った。年間を通して6台のエアロゾルゾンデを飛揚した。5) ドームふじ観測拠点における1997年の年平均気温は-54.4℃, 最低気温は7月8日に観測した-79.7℃であった。 This paper describes the results of meteorological observations at Syowa Station from February 1,1997 to January 31,1998,and at Dome Fuji Station from January 25,1997 to January 20,1998,carried out by the Meteorological Observation Team of the 38th Japanese Antarctic Research Expedition (JARE-38). The observation method, instruments, and statistical methods used by JARE-38 were almost the same as those used by the JARE-37 observation team. Remarkable weather phenomena observed during the period of JARE-38 are as follows; 1) Annual mean surface temperature in 1997 at Syowa Station was normal. The monthly mean temperature in September was -23.6℃, which was the lowest value in the historical record of Syowa Station. 2) The large scale Antarctic ozone hole was observed for the ninth successive year at Syowa Station. The lowest monthly mean total ozone amounts in 1997 was 164m atm-cm recorded in October. This was the second lowest value of October historical record at Syowa Station. 3) Surface ozone concentration was observed through the whole year at Syowa Station. A surface ozone depletion event was observed from 28 to 29 August 1997. 4) Stratospheric aerosols were observed with an optical particle counter sonde at Syowa Station. Six sondes were released and the annual variation was observed. 5) Annual mean surface temperature at Dome Fuji Station was -54.4℃; the lowest temperature was -79.7℃ observed on July 8th. departmental bulletin paper